LudusScope: Accessible Interactive Smartphone Microscopy for Life-Science Education. - Honesty Kim; Lukas Cyrill Gerber; Daniel Chiu; Seung Ah Lee; Nate J Cira; Sherwin Yuyang Xia; Ingmar H Riedel-Kruse (PLoS ONE, 2016)
For centuries, observational microscopy has greatly facilitated biology education, but we still cannot easily and playfully interact with the microscopic world we see. We therefore developed the LudusScope, an accessible, interactive do-it-yourself smartphone microscopy platform that promotes exploratory stimulation and observation of microscopic organisms, in a design that combines the educational modalities of build, play, and inquire. The LudusScope's touchscreen and joystick allow the selection and stimulation of phototactic microorganisms such as Euglena gracilis with light. Organismal behavior is tracked and displayed in real time, enabling open and structured game play as well as scientific inquiry via quantitative experimentation. Furthermore, we used the Scratch programming language to incorporate biophysical modeling. This platform is designed as an accessible, low-cost educational kit for easy construction and expansion. User testing with both teachers and students demonstrates the educational potential of the LudusScope, and we anticipate additional synergy with the maker movement. Transforming observational microscopy into an interactive experience will make microbiology more tangible to society, and effectively support the interdisciplinary learning required by the Next Generation Science Standards.